Interventions on design and political geography1. (October 2019) - Grove, Kevin; Krivý, Maroš; Rickards, Lauren; Schliwa, Gabriele; Collier, Stephen J.; Cox, Savannah; Gandy, Matthew
Abstract: This intervention seeks to focus political geographic attention on design as a form of governing emergent futures in the urbanized world of the Anthropocene. Recent decades have seen design shifting its concern from objects to processes, systems and futures. Design orients thought and action not towards questions of how something came to be, but rather what something might become, crafting new futures from within, rather than outside, the present. These "designerly" sensibilities are overtly and covertly reconfiguring how human-environment relations are studied across all scales, attuning urban governance around the world to a technocratic variant of the Anthropocene and to the "urban age" promulgated by complexity theory. In the process, they are opening onto an indeterminate political field over the possibilities for knowing, governing and contesting human-environment relations. On one hand, the post-historical impulses of resilience and smartness govern the urban as eco-cybernetic systems, discarding utopias and declaring politics and planning as obsolete. On the other hand, critical theorists have increasingly sought to decolonize design and deploy designerly strategies and techniques towards political projects that create new modes of collective becomings. Design is thus a novel and pressing field for political geographic research. The essays in this intervention avoid giving design a singular, essential definition, instead exploring, in their own ways, how political geographic thought might shine new light on the variety of contemporary efforts to know, manage and resist efforts to govern through complexity and uncertainty that fall under the umbrella of "design".